Pengaruh Penggunaan Media Kahoot terhadap Hasil Belajar Siswa pada Pembelajaran Akidah Akhlak di MAN 1 Padang Pariaman - Adria Nelisa Putri; Oktarina Yusra; Jasmienti Jasmienti; Fajriyani Arsya (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to analyze the effect of Kahoot media on student learning outcomes in Aqidah Akhlak learning in class X MAN 1 Padang Pariaman. The method used is quasi-experiment with Time Series Design and quantitative approach. The study population included 256 grade X students, with samples of class X.I as the control class and X.VI as the experimental class, each totaling 36 students, who were selected by simple randomization. Data were collected through an objective test with 25 questions. The results showed that the average student learning outcomes in the experimental class using Kahoot media reached 75.44%, higher than the control class of 67.89%. Hypothesis testing using SPSS 22.0 resulted in a significant value of 0.045 (α < 0.05), indicating that the use of Kahoot media significantly improved Aqidah Akhlak student learning outcomes. Thus, the research hypothesis is accepted.